The Effect of Reward, Punishment, and Organizational Commitment on Employee Performance with Job Satisfaction as an Intervening Variable in the Jember Regency Government - Fransiska Grassela Sucipto; Retno Endah Supeni; Abadi Sanosra (Universitas KH. Abdul Chalim Mojokerto, 2026)
Employee performance is a crucial element in achieving the effectiveness of public sector organizations. Efforts to improve performance depend not only on individual capabilities, but also on human resource management systems that are able to encourage motivation, job satisfaction, and work commitment. This study aimed to analyze the effect of reward, punishment, and organizational commitment on employee performance, with job satisfaction as an intervening variable in the Government of Jember Regency. This study was important considering the need for employee management strategies oriented toward improving performance and the quality of public services. This study employed a quantitative approach with an explanatory research design. Data were obtained from 300 Civil Servants within the Government of Jember Regency selected using proportional random sampling. Data were collected through structured questionnaires and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with WarpPLS 8.0 software to examine both direct and indirect relationships among variables. The results showed that reward, punishment, and organizational commitment had a positive and significant effect on job satisfaction. Reward had a positive but insignificant effect on employee performance. Punishment, organizational commitment, and job satisfaction had a positive and significant effect on employee performance. Job satisfaction was proven to mediate the effect of reward, punishment, and organizational commitment on employee performance. These findings indicate that reward policies do not always have a direct impact on performance improvement, but become more effective when they are able to enhance employee job satisfaction. This study provides theoretical contributions by strengthening the role of job satisfaction as a mediating mechanism, as well as practical contributions for local governments in designing a fairer, adaptive, and results-oriented performance management system.